A methodology of design for seismic performance enhancement of buildings using viscous fluid dampers. Issue 3 (17th April 2013) - Rama Raju, K.; Ansu, M.; Iyer, Nagesh R.
SUMMARY A methodology of design for seismic performance enhancement of buildings by using linear viscous fluid dampers (VFDs) is proposed. It also gives the procedure for arriving at an efficient distribution of VFDs in the building. The peak base shear and inter‐storey drifts determined from a time history analysis of the building subjected to design basis earthquake (DBE) are used for satisfying the Uniform Building Code 1997 specified target performance criteria for base shear and inter‐storey drifts. The methodology proposed is used for designing the linear VFDs to increase the effective damping with chevron, upper toggle, and scissor jack mechanisms in a 20‐storey benchmark building subjected to DBE to meet the performance criteria. The time histories of the N–S component of El Centro, N–S component of Kobe, N–S component of Northridge, and S–E component of Taft scaled to a PGA of 0.2 g are considered to be representatives of DBE for the place where the 20‐storey benchmark building is located. It is observed that the optimum location of the dampers with different mechanisms in the building is the ground floor or the first few storeys from the ground floor. Copyright © 2013 John Wiley & Sons, Ltd.